PERENCANAAN KEBUTUHAN AREAL PARKIR DI PASAR B LAWANG TIGO BALAI KECAMATAN MATUR KAB. AGAM - Rantih Oktavianus; Deddy Kurniawan; Ana Susanti Yusman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Parking is defined as an activity to put or store vehicles in a certain place whose duration depends on the completion of the needs of the driver, so a parking space is needed. This research was conducted to plan the index of parking area processing needs in the market B Lawang Tigo Balai, Matur District, Kab. religion. The data or information used is in the form of primary data obtained from field observations and secondary data obtained from Market B Lawang Tigo Balai. So, it is necessary to plan the processing of parking spaces at Pasar B Lawang Tigo Balai which can increase the need for a more optimal parking area and manage a comfortable parking space. From the results of the calculation analysis, it is found that the maximum accumulation of parking in the wali nagari office area occurs on Friday as many as 200 vehicles, the maximum accumulation of parking in the Jami' mosque area occurs on Friday as many as 320 vehicles and the maximum accumulation of parking in the parking area behind the market occurs on Friday as many as 40 vehicles. From the results of the calculation analysis, it is found that the parking duration at the motorbike parking turnover rate in the Wali Nagari Office area is high on Friday at 2.19 SRP. The duration of parking at the motorcycle parking turnover rate at the Jami' Mosque occurred on Friday at 1.08 SRP.The duration of parking at the car park turnover rate behind the market occurred on Friday at 2.53 SRP. From the results of the calculation analysis, it was found that the average motorcycle parking index at the Wali Nagari office was 116.33%, a parking index greater than 100%. shows that the capacity of the parking space at the wali nagari office is no longer able to accommodate the demand for motorcycle parking. The average motorcycle parking index at the Jami' Mosque office is 51.33%, a parking index that is greater than 100% indicates that the parking space capacity at the Jami' Mosque is no longer able to accommodate vehicle parking requests. The average behind-the-market car parking index is 127.43%, a parking index greater than 100% indicates that the parking space capacity behind the market is no longer able to accommodate the demand for motorcycle parking.Keywords: Parking Area Planning, Parking Accumulation, Parking Duration and Parking Index.